Stakeholders’ Perspectives on Child Healthcare Services under Rural Health Reform in Thailand: A Qualitative Study - Katemanee Moonpanane; Salisa Kodyee; Pimkanabhon Trakooltorwong; Kunnara Maneekunwong; Chompunut Sopajaree (International Journal of Community Based Nursing and Midwifery)
Background: Children under 5 years old are a global health priority; however, healthcare services for this age group remain limited, especially in rural areas of Thailand. This study explores the perspectives of stakeholders responsible for child healthcare delivery in resource-constrained rural communities.Methods: This study is a qualitative research using thematic framework analysis. Participants (N=45) including twenty parents, ten healthcare providers, five village health volunteers, five teachers, and five community leaders were recruited using purposive sampling. In-depth interviews and focus group discussions, lasting between 40 and 70 minutes, were performed to explore the participants’ perspectives. Data were collected from February to November 2021. All interviews were transcribed and analyzed using NVivo software version 21.Results: The research identified two themes, each with two sub-themes: 1) Structural limitations: disparity in the distribution of service and healthcare provider training and challenges in policy implementation, and 2) Opportunities to optimize childcare: fostering community ownership and multidisciplinary collaboration and strengthening family engagementConclusions: This study revealed significant challenges and opportunities in delivering healthcare services to children in rural Thailand. The findings underscore the importance of coordinated interventions that enhance community involvement and strengthen family engagement.